COMPARATIVE AND QUANTITATIVE DETERMINATION OF QUERCETIN AND OTHER FLAVONOIDS IN NORTH INDIAN POPULATIONS OF TRIBULUS TERRESTRIS LINN, BY HPLC - ASHWANI KUMAR (International Journal of Pharma and Bio Sciences, 2012)
Tribulus terrestris extract has an ancient tradition in folk medicine and in ayurveda as a diuretic, mood enhancer, antiseptic and anti-inflammatory agent. Six populations of Tribulus terrestris were studied in North India at different ecological habitats. Populations have different phenotypes and chemotypes. We detected two main and other flavonoid components of this plant by TLC and HPLC in different quantity. Altogether 18-28 flavonoid compounds were detected in the populations by HPLC with very different flavonoid patterns. Plants living at shadowy habitats were higher; they had more leafy branches, leaves and more (9-13) flavonoid constituents. Populations living at sunny areas had smaller stem and leaves, and only 4-9 flavonoid compounds. According to the morphology and flavonoid pattern, the populations were classified into ecotype groups, which can be related to the studied ecological habitats. These results prove that Tribulus terrestris L. is a very polymorph plant species, leading to have a wide pool of phytomedicinal components (flavonoids) in relation to its geographic condition and cytological behavior. In future high drug yielding plants can be used to prepare particular pharmaceutical formulations.